IMPLEMENTASI ROUTING EIGRP PADA JARINGAN KOMPUTER - ACHMAD ACHMAD (LPPM, 2016)
EIGRP (Enhanced Interior Gateway Routing Protocol) is the routing protocol only adopted by a Cisco router or often referred to as the Cisco proprietary protocol. Where EIGRP neighbor can only be used cisco router. The point is, EIGRP router function to connect one with the other routers by introducing network-network on every interface that is on the router itself, is the result of the development of its predecessor IGRP routing protocol that both the development of CISCO routing. The development was generated by changes and diverse demands of large-scale network network. EIGRP combines the capabilities of a Link-State Protocol and Distance Vector Protocol, moreover EIGRP protocol contains several important that both improve the efficiency of its use to another routing protocol. EIGRP implementation goal for knowing and learning how EIGRP routing process mechanism of each router so that the computer network can be connected by pinging testing to each computer.Keyword: EIGRP, Routing Protocol.